Symmetric multiple ulceration in a patient diagnosed with Munchausen syndrome. Issue 1 (6th October 2021) - Inoue, Emi; Kakuda, Kasumi; Fujiwara, Midori; Yokoi, Kazunori; Koguchi‐Yoshioka, Hanako; Kiyohara, Eiji; Hata, Masahiro; Kanai, Koji; Fujimoto, Manabu; Tanemura, Atsushi
Abstract : We experienced a rare case of Munchausen syndrome with peculiar symmetric ulcers on the whole body. When encountering similar cases with factitious ulceration of the skin, a thorough understanding of the patient's psychiatric condition and a cordial consultation to present illness rather than physical medication might lead to disease stability.